2018
DOI: 10.1037/pspi0000119
|View full text |Cite
|
Sign up to set email alerts
|

Motivation moderates the effects of social support visibility.

Abstract: Social support can sometimes have negative consequences for recipients. One way of circumventing these negative effects is to provide support in an 'invisible' or indirect manner, such that recipients do not construe the behavior as a supportive act. However, little is known about how recipients' motivational states influence when visible (direct) support or invisible support is more beneficial. Using the framework of Regulatory Mode Theory, we predicted that recipients motivated to engage in critical evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 64 publications
2
52
0
Order By: Relevance
“…Although additional work would help elucidate whether stress is a boundary condition, it seems likely that perceived movement might also mediate the effects of locomotion motivation when support is given for stressful events. Other findings, for instance, showed that recipients with a predominant locomotion motivation coped better (e.g., their stress reactivity and distress were lower) when they received experimentally manipulated visible (explicit) support for a stressful speech (Zee et al, ). Although perceived movement was not measured, the manipulations used in this research contained tangible information about how the participant was coping with the stressor.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although additional work would help elucidate whether stress is a boundary condition, it seems likely that perceived movement might also mediate the effects of locomotion motivation when support is given for stressful events. Other findings, for instance, showed that recipients with a predominant locomotion motivation coped better (e.g., their stress reactivity and distress were lower) when they received experimentally manipulated visible (explicit) support for a stressful speech (Zee et al, ). Although perceived movement was not measured, the manipulations used in this research contained tangible information about how the participant was coping with the stressor.…”
Section: Discussionmentioning
confidence: 99%
“…Prior work has shown that people higher on locomotion benefit from overt social support interactions (Kumashiro et al, ; Zee et al, ). This study extends knowledge of locomotion and support by showing that perceived movement toward their goals mediates the association between recipient locomotion and beneficial outcomes in support contexts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations